Phycoremediation of wet market wastewater using microalgae scenedesmus sp. For biomass production - Mohd Apandi, Najeeha (2019)
Rapid industrial development and escalating population growth are expected to contribute extremely to the world’s environmental crisis due to excessive wastewater generation. Therefore, a technology by phycoremediation to reduce the wastewater contamination, coupled with biomass production of sustainable bioproduct has attracted interest worldwide. Thus, the aim of the study is to generate a potential bioproduct from microalgae Scenedesmus sp. combined with phycoremediation of wet market wastewater (WMW). The optimization study proved that the Scenedesmus sp. grew up well in the temperature between 24-32ºC, light intensity of 245 μmol m-2s-1 and 18 hours of light exposure. In fact, this Scenedesmus sp. was much more tolerated in outdoor condition when integrated with wastewater phycoremediation in terms of biomass productivity and wastewater bioremediation. The best microalgae concentration was performed at 106cell/mL during phycoremediation process using WMW. The highest removal of nutrients (TP, TN and TOC) in WMW was up to 85%, 90% and 65% respectively under outdoor condition. Selected heavy metals (Cd, Cr, Fe, Pb and Zn) removed 87.24%, 85.55%, 90.35%, 88.5% and 87.1%, respectively. In microalgae cultivation, this study notably found the optimum of 64.26% of WMW concentration and 3.07 L/min of aeration rate were established by using statistical analysis by response surface design (RSM) in terms of biomass productivity with 6% error for the validation experiment with the value of biomass production of 68.32 mg/L/d. Besides that, the total protein and lipid content in the biomass yield produced in WMW (41.7% and 23.2%) which were more than the biomass produced in the BBM (37.4 and 19.2% respectively). The main functional of fatty acid detected 30 compounds in the biomass from WMW compared to 6 compounds in the BBM. This study notably found that WMW is a suitable and worthy media to be implemented in Scenedesmus sp. cultivation. Moreover, the quality composition of protein, lipid and fatty acid compound also have a bright perspective to be used as fish feed, agro feedstock, biodiesel and pharmaceutical potential and any related industry.